1998
DOI: 10.4141/s98-009
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide production in soils cropped to corn with varying N fertilization

Abstract: . 1998. Nitrous oxide production in soils cropped to corn with varying N fertilization. Can. J. Soil Sci. 78: [589][590][591][592][593][594][595][596]. Mineral N fertilizers may contribute to N gas emissions to the atmosphere. Soil cores were collected in 1993 and 1994, in a sandy loam and a sandy clay cropped with an early-maturing corn (Zea mays L.) hybrid and fertilized with ammonium nitrate at rates of 10, 60, 120 or 180 kg N ha -1 . Denitrification and N 2 O production rates, air-filled porosity (AFP), wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 32 publications
5
45
1
1
Order By: Relevance
“…This has been reported under maize [17,18] and spring barley [19]. Under these conditions, and when conditions are also conducive to denitrification, splitting fertilizer N applications could reduce N 2 O losses.…”
Section: Reduce Losses (B)mentioning
confidence: 67%
“…This has been reported under maize [17,18] and spring barley [19]. Under these conditions, and when conditions are also conducive to denitrification, splitting fertilizer N applications could reduce N 2 O losses.…”
Section: Reduce Losses (B)mentioning
confidence: 67%
“…High spring rainfall could have triggered losses of fertiliser N applied at pre-seeding by denitrification and/or leaching. Lower air-filled porosity and very high N 2 O production were reported by Chantigny et al (1999) on a Kamouraska sandy clay in June 1994 as compared with 1993. These very wet conditions in the St-Lawrence lowlands may have resulted in less plant-available N in 1994 than in 1993 and 1995.…”
Section: Discussionmentioning
confidence: 72%
“…Liang and MacKenzie (1997) found that for a sandy clay loam in the St. Lawrence lowlands losses of NO 3 -by denitrification were related to soil moisture in April and May. Chantigny et al (1999) reported that denitrification rates were inversely related to air-filled porosity. For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…VWC and WFP for the Lower Longley, Lucaston and the inter-row at Young showed an atypical significant negative (weak) influence on N 2 O emissions. Elevated emissions are linked to WFP > 60% (Chantigny et al 1998;Helgason et al 2005) and VWC > 0.55 cm 3 cm -3 (van der Weerden et al 2012), conditions rarely seen in the orchards during the study period. For these sites, during winter when WFP and VWC were highest, soil temperatures were extremely low and accounted for the negative correlation observed and the moderately negative correlation between VWC and N 2 O emissions in winter (r = -0.506).…”
Section: Temporal and Spatial Variability Of N 2 O Emissionsmentioning
confidence: 99%